Design a visual dot probe task for occupational stress measurement in manufacturing - Chong, Kai Wen (2024)
Job-related stress is a crucial but frequently disregarded problem within the manufacturing industry, where it affects individual well-being severely. This study introduces a visual dot probe task prototype developed to assess stress levels by leveraging attentional biases and responses to emotional stimuli. The prototype will be validated using the Perceived Stress Scale (PSS-10) in terms of stress level, while its usefulness and ease of use are evaluated through the Technology Acceptance Model (TAM). The research involved 21 participants from the manufacturing industry who underwent stress testing using the dot probe task prototype and completed two questionnaires, including the PSS-10 and the TAM, to measure stress perception of participants and prototype acceptance, respectively. The visual dot probe task prototype includes 40 trials to assess stress levels using emoji-based stimuli, distinguishing between congruent and incongruent trials, with participants responding to dot locations. High reliability was shown by Cronbach's alpha tests for both PSS-10 (α = 0.866) and TAM (α = 0.976). Descriptive statistics for PSS-10 revealed a moderate stress level (mean range: 1.86 to 2.43) and TAM responses indicated strong acceptance (mean range: 3.43 to 3.91). The visual dot probe task exhibited a congruent trial reaction time of 422.23ms, incongruent trial reaction time of 447.69ms, and an attentional bias score of -25.46ms. Pearson correlations revealed a strong positive correlation between congruent and incongruent reaction times (r = 0.944), while attentional bias score showed weaker correlations. A t-test confirmed significant differences between congruent and incongruent reaction times. Comparisons between PSS-10 scores and dot probe task variables demonstrated a moderate negative correlation. T-tests confirmed statistically significant differences between PSS-10 scores and dot probe task variables. Therefore, the visual dot probe task successfully measured attentional biases, demonstrating its usefulness and ease-of-use in the manufacturing industry. This offers a promising alternative for stress assessment and contributes to employee well-being in manufacturing.